PERLINDUNGAN HAK KONSUMEN AKIBAT ATURAN KLAUSULA BAKU USAHA KARAOKE KELUARGA DI PEKANBARU DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Astari, Fenty Rizka; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Consumers protection is all means which guarantee the legal security to protect the consumers.Consumer protection laws are a form of government regulation, which aim to protect the rights of consumers. The original basic consumer rights are: the right to choose, the right to safety, the right to be informed, and the right to be heard. Consumers rights and consumer protection law provides a way for individuals to fight back against unfair business practices. A consumer should have the opportunity to select the goods or services that he or she wants to purchase without any restrictions of right. For example, thereis standard clause. Standard Clause is any regulations or provisions and conditions unilaterally prepared and predetermined by the entrepreneurs in the form of a document and/or an agreement which is binding and must be met by the consumers. In offering the goods and/or services for trading, the entrepreneurs are prohibited from making or including a standard clause on each document and/or agreement if, point (g) it states that the consumers are subject to the new regulation, additional regulation, continued regulation and/or continuous change of regulation made unilaterally by entrepreneurs during the period the consumers are using the services they purchased.Key Words: Consumers Protection – Basic Consumer Rights – Standard Clause